DHA supplementation in infants born preterm and the effect on attention at 18 months' corrected age: follow-up of a subset of the N3RO randomised controlled trial. Issue 4 (28th February 2021) - Hewawasam, Erandi; Collins, Carmel T.; Muhlhausler, Beverly S.; Yelland, Lisa N.; Smithers, Lisa G.; Colombo, John; Makrides, Maria; McPhee, Andrew J.; Gould, Jacqueline F.
Abstract: Infants born preterm miss out on the peak period of in utero DHA accretion to the brain during the last trimester of pregnancy which is hypothesised to contribute to the increased prevalence of neurodevelopmental deficits in this population. This study aimed to determine whether DHA supplementation in infants born preterm improves attention at 18 months' corrected age. This is a follow-up of a subset of infants who participated in the N3RO randomised controlled trial. Infants were randomised to receive an enteral emulsion of high-dose DHA (60 mg/kg per d) or no DHA (soya oil – control) from within the first days of birth until 36 weeks' post-menstrual age. The assessment of attention involved three tasks requiring the child to maintain attention on toy/s in either the presence or absence of competition or a distractor. The primary outcome was the child's latency of distractibility when attention was focused on a toy. The primary outcome was available for seventy-three of the 120 infants that were eligible to participate. There was no evidence of a difference between groups in the latency of distractibility (adjusted mean difference: 0·08 s, 95 % CI –0·81, 0·97; P = 0·86). Enteral DHA supplementation did not result in improved attention in infants born preterm at 18 months' corrected age.